2022
DOI: 10.20473/brpkm.v2i1.36518
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Kecerdasan Emosional dengan Work-life Balance pada Karyawan Startup

Abstract: Tujuan dari penelitian ini adalah untuk mengetahui apakah kecerdasan emosional memiliki hubungan dengan work-life balance pada karyawan startup. Startup memiliki jam kerja yang fleksibel dan fast paced, sehingga waktu karyawan banyak dihabiskan untuk bekerja. Maka dari itu dibutuhkan kecerdasan emosional untuk dapat menentukan peran sesuai dengan situasi yang dibutuhkan. Meskipun begitu, terdapat penelitian lain yang memiliki hasil berlawanan. Metode yang digunakan adalah metode survei dengan teknik non-probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…Nineteen research reports identified a correlation between work-life balance and positive mental health among employees. [58,59,[68][69][70][71][72][73][74][75][76][60][61][62][63][64][65][66][67] We note positive variations in mental health that have a positive relationship with work-life balance, including psychological well-being, resilience, life satisfaction, wellbeing, good mental health, higher job satisfaction, lower turnover intention, psychological well-being, mental wellbeing, job performance, and job engagement.…”
Section: Discussion Association Between Work-life Balance and Positiv...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen research reports identified a correlation between work-life balance and positive mental health among employees. [58,59,[68][69][70][71][72][73][74][75][76][60][61][62][63][64][65][66][67] We note positive variations in mental health that have a positive relationship with work-life balance, including psychological well-being, resilience, life satisfaction, wellbeing, good mental health, higher job satisfaction, lower turnover intention, psychological well-being, mental wellbeing, job performance, and job engagement.…”
Section: Discussion Association Between Work-life Balance and Positiv...mentioning
confidence: 99%
“…Nineteen studies examine the association between worklife balance and positive employee mental health. [58,59,[68][69][70][71][72][73][74][75][76][60][61][62][63][64][65][66][67] This study was conducted in Malaysia, South Korea, India, Indonesia, Pakistan, Nigeria, Ghana, Australia, China, the United Kingdom, Chinese, New Zealand Maori, New Zealand European, Spanish, French, and Italian, Brazil, and Canada.…”
Section: Is There An Association Between Work-life Balance and Positi...mentioning
confidence: 99%
“…Menurut Robbins (Tentama, 2015) kepuasan kerja adalah sikap secara umum dan tingkat perasaan positif individu terhadap pekerjaannya. Robbins (Nugraha, 2018) menyatakan bahwa sikap ini diperlihatkan pada moral kerja, kedisiplinan, prestasi kerja, umpan balik, penempatan, perlakuan, peralatan, suasana lingkungan kerja, dan mendapatkan pujian akan hasil kerja yang sudah dilakukan. Jika karyawan tidak mendapatkan kepuasan dalam bekerja akan menimbulkan sikap kerja yang tidak baik dan memberikan dampak negatif kepada perusahaan.…”
unclassified